SURGICAL MANAGEMENT OF ACUTE EMBOLIC LIMB ISCHEMIA - AN EXPERIENCE OF 256 CASES - Muhammad Jamil; Rashid Usman (Journal of University Medical & Dental College, 2015)
ABSTRACTOBJECTIVES: To highlight the importance of embolectomy in patients with acute embolic limb ischemia.STUDY DESIGN: Descriptive analytic study.PLACE AND DURATION OF STUDY: The Department of Vascular Surgery, Combined Military Hospital Lahore, from July 2008 to April 2015.PATIENTS AND METHODS: 256 consecutive patients having acute limb ischemia who underwent embolectomy were included in this study. Embolectomy was done with Fogarty catheter under local anaesthesia; using femoral, popliteal and brachial approaches.RESULTS: Two hundred and ﬁfty six patients with acute embolic limb ischemia were treated surgically by embolectomy. The lower limbs were effected in 167 (65.2%) and upper limb in 89 (34.7%) cases. Male female ratio was 1.5: 1. Only 11 patients (4.2%) reported within 6 hours of onset of ischemic symptoms. 147 patients (57.4%) reported after 12 hours. Embolism was the commonest cause. Most frequent site for obstruction was femoral bifurcation (45.3%). Skin discoloration and presence of motor paralysis were poor prognostic signs. Only in 25 patients (9.8%) fasciotomy along with embolectomy was performed. 26 patients required amputations (9.9%). Limb salvage rate was 83.5% (214 patients).CONCLUSION: Simple Embolectomy is time tested and safest surgicalprocedure in the management of acute embolic limb ischemia